Kesantunan Berbahasa Orang Tua dan Anak pada Youtube “Bolehkah Sekali Saja Kumenangis” - Amiruddin, Nurlina; Martutik, Martutik; Susanto, Gatut (Universitas Muhammadiyah Surakarta, 2025)
This study aims to describe the form of politeness in language by Prilly and her father in a video entitledSocial Experiment: “Can I cry just once?